i know it equals x^2 but I have no idea how to get that. i need to know HOW to solve it not what the answer is.

Rules of logarithms.
alogb=log(b^a)
so then
e^(2lnx)=e^[ln(x^2)]
then the e and natural log cancel out leaving you with (x^2)
Hope that explains it :)
alogb=log(b^a)
so then
e^(2lnx)=e^[ln(x^2)]
then the e and natural log cancel out leaving you with (x^2)
Hope that explains it :)

e^(2lnx) = e^(ln(x^2)
= x^2
= x^2

y = e^(2lnx)
Take ln,
lny = 2lnx = lnx^2
So, y = x^2
Take ln,
lny = 2lnx = lnx^2
So, y = x^2